2020
DOI: 10.1155/2020/6769726
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile of Nipa Palm Vinegar and Evaluation of Its Antilipidemic Activities

Abstract: Obesity and overweight are strongly associated with dyslipidemia which can promote the development of cardiovascular diseases. Recently, natural products have been suggested as alternative compounds for antioxidant and antilipidemic activity. The objective of this study was to determine the phenolic compounds and assess the inhibitory activities on pancreatic lipase, cholesterol esterase, and cholesterol micellization of nipa palm vinegar (NPV). Total phenolic content was assessed and phenolic compounds were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Several studies reported that phenolic compounds are involved in lipase and cholesterol esterase inhibition activities [7,19,[46][47][48]. Thus, the inhibitory activities of these enzymes in this study might be attributed to the presence of 7-O-methyl luteolin 5-O-β-D-glucopyranoside, chrysoeriol 5-O-β-D-glucopyranoside, 5,7-dihydroxy-3,2 ′ ,4 ′ -trimethoxyflavone, and plectranmicin revealed as major compounds in both hydroethanolic and ethyl acetate extracts through LC-HRMS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that phenolic compounds are involved in lipase and cholesterol esterase inhibition activities [7,19,[46][47][48]. Thus, the inhibitory activities of these enzymes in this study might be attributed to the presence of 7-O-methyl luteolin 5-O-β-D-glucopyranoside, chrysoeriol 5-O-β-D-glucopyranoside, 5,7-dihydroxy-3,2 ′ ,4 ′ -trimethoxyflavone, and plectranmicin revealed as major compounds in both hydroethanolic and ethyl acetate extracts through LC-HRMS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this has led to the search of novel lead molecules, preferably from natural products possessing antilipidemic and antithrombotic properties with lesser or no side effects and that are affordable to a large spectrum of population compared to the existing antilipidemic and antithrombotic drugs. Interestingly, a large number of earlier studies have reported many plant secondary metabolites, especially phenolic compounds, and have good inhibitory effects toward digestive enzymes such as pancreatic lipase and cholesterol esterase enzymes [7,[18][19][20]. Dietary polyphenols may also suppress the growth of adipose tissue through their antiangiogenic activity and by modulating adipocyte metabolism [21], as well as thrombolytic activity by dissolving blood clots [22].…”
Section: Introductionmentioning
confidence: 99%
“…The nipa palm sap was fermented to NPV by the traditional local method ( Chatatikun & Kwanhian, 2020 ). The procedure, in brief, collect nipa palm sap from the cut stems and placed it in a terracotta tank at room temperature for 40 days to allow the natural fermentation process.…”
Section: Methodsmentioning
confidence: 99%
“…According to the procedure described in our previous work, the amount of total phenolic in NPV was determined by Folin-Ciocalteu assay ( Chatatikun & Kwanhian, 2020 ). First, 20 µL of samples were mixed with 100 µL of Folin-Ciocalteu reagent and 80 µL of sodium carbonate solution (75 g/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation